TEACHING AIMS OF THE ENGLISH LANGUAGE FOR SPECIFIC PURPOSES - Filimonova, Liliya Yurevna (Журнал иностранных языков и лингвистики, 2023)
The article considers some particular aspects, which teachers should keep in mind while teaching English as a part of engineering professional education. Practical, educational and cultural aims will be presented in this article.